A smooth muscle-specific monoclonal antibody recognizes smooth muscle actin isozymes (The Rockefeller University Press, 1985)
Injection of chicken gizzard actin into BALB/c mice resulted in the isolation of a smooth muscle-specific monoclonal antibody designated CGA7. When assayed on methanol-Carnoy's fixed, paraffin-embedded tissue, it bound to smooth muscle cells and myoepithelial cells, but failed to decorate striated muscle, endothelium, connective tissue, epithelium, or nerve. CGA7 recognized microfilament bundles in early passage cultures of rat aortic smooth muscle cells and human leiomyosarcoma cells but did not react with human fibroblasts. In Western blot experiments, CGA7 detected actin from chicken gizzard and monkey ileum, but not skeletal muscle or fibroblast actin. Immunoblots performed on two-dimensional gels demonstrated that CGA7 recognizes gamma-actin from chicken gizzard and alpha- and gamma-actin from rat colon muscularis. This antibody was an excellent tissue-specific smooth muscle marker.